Imprint of Southern Ocean eddies on winds, clouds and rainfall - Frenger, Ivy; Gruber, Nicolas; id_orcid:0 000-0002-2085-2310; Knutti, Reto; Münnich, Matthias; id_orcid:0 000-0003-3292-2934 (Nature Geoscience, 2013)
ISSN:1752-0908 ISSN:1752-0894